The science of gymnastics - Jemni, Monem (Routledge, 2011)
Examines the key aspect of gymnastic training and performance, including - physiological assessment; diet and nutrition; energetic; strength and conditioning; growth and development; anthropometric and biomechanical models; kinetics and kinematics; stress, anxiety and coping; and, motivation and goal setting.